Profiling of 520 Candidate Genes in 50 Surgically Treated Chinese Small Cell Lung Cancer Patients - Yuan, Ting; Wang, Xin; Sun, Sijin; Cao, Zheng; Feng, Xiaoli; Gao, Yibo (Frontiers in Oncology, 2021)
Small cell lung cancer (SCLC) is one of the severe malignancies with high mortality. Surgically resected tumor tissues from 50 Chinese SCLC patients were collected for next-generation sequencing to detect 520 cancer‐related genes. The most frequently altered genes were TP53 (94.0%), RB1 (86.0%), LRP1B (44.0%), SPTA1 (26.0%) and KMT2D (24.0%). We detected that NOTCH2, JAK2 and CDK12 (P<0.05) had a significantly higher mutation frequency in Chinese SCLC compared to the Cologne and MSKCC. The single nucleotide variation (SNV) is dominated by C>A (34.1%). We found a significant association between TMB-H (≥10.3muts/Mb) and ATM (P=0.023), CREBBP (P=0.010), KMT2D(P=0.050) and LRP1B (P=0.005) gene mutations in Chinese SCLC patients. Immunostaining was performed using the following antibodies: TTF-1, CgA, CD56, Syn, and Ki-67. Correlation analysis between the expression of 6 markers and mutations in signaling pathways showed that Syn and CgA expression were associated with 4 (cGMP-PKG, Chemokine, TGF-β and Phospholipase D) and 2 (cGMP-PKG and Phosphatidylinositol) signaling pathway mutations. Kaplan-Meier curve showed that age<55 years, mutant ARID2 and high TMB (≥7muts/Mb) were associated with a better prognosis, while the prognosis of patients with mutations in the Ras pathway was significantly improved. High TMB is an important prognostic factor for SCLC patients showed by multivariate analysis. In the combined cohort composed of current and two previous studies, survival analysis showed that SCLC patients with mutant LRP1B demonstrated better OS (P=0.0017). Patients with a high TMB (≥7muts/Mb) have a better prognosis (P=0.0053), consistent with our results in the Chinese cohort. We characterized the genomic alterations profile of Chinese SCLC patients and analyzed the correlation between genomic changes and immunohistochemical phenotypes at the signaling pathway level. Our data might provide useful information in the diagnosis and treatment for Chinese SCLC patients.